Optimal Trajectory Planning of Aircraft for Fair-Sharing of Noise. Issue 8 (2019) - Saito, Y.; Yoshimura, S.; Inoue, M.; Takahashi, M.; Sugihara, Y.
Abstract: In this paper, we propose a trajectory planning of aircraft to ensure the reduction and fair-sharing of aircraft noise. The fair-sharing of noise is realized by dispersing aircraft trajectories. The proposed trajectory planning consists of two stages. In the first stage, a performance index, which evaluates the accumulated noise for all areas, is calculated. The index, which takes into account noise accumulation, plays an essential role for trajectory dispersion. In the second stage, using the index, an optimization problem of planning aircraft trajectories is solved. Repeating these stages in a day, we realize to reduce and spatially share the noise. The effectiveness of the method is verified in a numerical experiment with actual flight data.